The Influence of Cognitive Dual Tasking on the Outcomes of the Triple Hop Test Following Anterior Cruciate Ligament Reconstruction - Roberto Ricupito; Alberto Grassi; Matteo Zanuso; Paolo Torneri (International Journal of Sports Physical Therapy)
# Introduction